Molecular mechanism of J-domain-triggered ATP hydrolysis by Hsp70 chaperones - Kityk, Roman; Kopp, Jürgen; Mayer, Matthias P. (Molecular cell, 2018)
Efficient targeting of Hsp70 chaperones to substrate proteins depends on J-domain cochaperones, which in synergism with substrates trigger ATP hydrolysis in Hsp70s and concomitant substrate trapping. We present the crystal structure of the J-domain of Escherichia coli DnaJ in complex with the E. coli Hsp70 DnaK. The J-domain interacts not only with DnaK's nucleotide-binding domain (NBD) but also with its substrate-binding domain (SBD) and packs against the highly conserved interdomain linker. Mutational replacement of contacts between J-domain and SBD strongly reduces the ability of substrates to stimulate ATP hydrolysis in the presence of DnaJ and compromises viability at heat shock temperatures. Our data demonstrate that the J-domain and the substrate do not deliver completely independent signals for ATP hydrolysis, but the J-domain, in addition to its direct influence on Hsp70s catalytic center, makes Hsp70 more responsive for the hydrolysis-inducing signal of the substrate, resulting in efficient substrate trapping.
Gesehen am 15.10.2018
Available online 28 December 2017